Arterias. (Malmö : Konsthall, 1998)
Badiola, Txomin ; Baselitz, Georg ; Charlton, Alan ; Clemente, Francesco ; Cragg, Tony (Anthony) ; Croft, José Pedro ; Deacon, Richard ; Dorner, Helmut ; Dujourie, Lili ; Fritsch, Katarina ; Gordillo, Luis ; Gröting, Asta ; Gursky, Andreas ; Halley, Peter ; Irazu, Pello ; Lasker, Jonathan ; Mangold, Robert ; Martin, Agnes ; Moreno, Felicidad ; Muñoz, Juan ; Hernandez Pijuan, Juan ; Polke, Sigmar ; Richter, Gerhard ; Rollins, Tim & K.O.S. ; Ruff, Thomas ; Ryman, Robert ; Scully, Sean ; García Sevilla, Ferran ; Solano, Susana ; Steinbach, Haim ; Tàpies, Antoni ; Therrien, Robert ; Uslé, Juan ; Vermeiren, Didier
biografie
Arterias, Konsthall Malmö, 25.4 - 7.6.1998
kunstcatalogus